Communicative Strategies to Respond to IELTS Essay Writing Questions: The Case in Band 7 - Warsidi, Warsidi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study intends to analyze communicative strategies to respond to IELTS essay writing questions. It used a genre-based approach for the analysis, using 20 IELTS essay writing samples and receiving band seven. The results revealed that IELTS test takers in this study employed two communicative strategies to respond to questions: presenting introductory responses and responding to questions either explicitly or implicitly. However, while they used simple sentences more than the other sentence types in presenting introductory responses, they used more complex sentences to respond to the questions. Then, they tend to write these two communicative strategies in simple present tense forms. The implications of these findings are discussed in the discussion section.